IDENTIFIKASI MISKONSEPSI MENGGUNAKAN CRI DAN PENYEBABNYA PADA MATERI MEKANIKA FLUIDA KELAS XI SMA (UPEJ Unnes Physics Education Journal, 2017)
This study aimed to determine variety of students misconception, as well as its causes and impact. Design of the study was a survey study, which was a study to collect data from a certain natural place (not created one), but the researcher did a treatment in collecting data. Samples were taken by using purposive sampling method, and they were classes of XI IPA 3 and XI IPA 5. The samples were collected by observation, documentation, questionnaire, test and interview. Result of study indicated that highest level of knowing the concept was on fluids and static fluids concepts as much as 40,2%, level of knowing-but-not-sure was on adhession and cohession concept as much as 11,8%, while the highest level of misconception was on Archimedes law concept as much as 54,5% and the highest level of not-knowing was on viscosity and its units concept as much as 72,5%. There were some factors causing the students misconception, such as, learning process, students thinking way, material books, experience and lack of knowledge.